PENGARUH MINAT BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI SISWA KELAS VIII PADA MATA PELAJARAN IPS DI TAMAN DEWASA (SMP) TAMAN SISWA TAHUN AJARAN 2023/2024 - Onaria Damanik; Anggun Tiur Ida Sinaga; Herlina Hotmadinar Sianipar (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to gain knowledge regarding the influence of learning interest and learning motivation on the achievement of class VIII students in social studies subjects at Taman Siswa Adult School (SMP) for the 2023/2024 academic year.This type of research is quantitative research with the testing media used is Microsoft Excel. The total population in this study was 76 people, and the sample used was 76 people. The sampling technique used was a saturated sample. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2).The research results state that: 1) there is a positive influence of interest in learning on student achievement. This result can be seen in the t test where the t value of interest in learning (3.289) > t table value (1.665). 2) there is a positive and significant influence of learning motivation on student achievement. This result can be seen in the t-test for learning motivation (4.446) > t table value (1.665) which means the variable is significant. 3) interest in learning and motivation to learn together influence student achievement. This result can be seen in the F test where the fcount value (37.625) > ftable value (31.221). The R Square coefficient of determination test was found to be 33.53, which means that 33.5% of the variables of interest in learning and motivation to learn have an influence on the achievement of class VIII students in Taman Siswa for the 2023/2024 academic year and 66.47% is the influence of the variables. others not examined in this research.